Unpacking intoxication, racialising disability. Issue 1 (7th June 2015) - Chen, Mel Y
Abstract : This article examines concepts whose strictly medical applications have only partly informed their widespread use and suggests that demonstrably shared logics motivate our thinking across domains in the interest of a politically just engagement. It considers exchanges between the culturally complex concepts of 'toxicity' and 'intoxication', assessing the racialised conditions of their animation in several geopolitically—and quite radically—distinct scenarios. First, the article sets the framework through considering the racial implications of impairment and disability language of 'non-toxic' finance capital in the contemporary US financial crisis. Shifting material foci from 'illiquid financial bodies' to opiates while insisting that neither is 'more' metaphorically toxic than the other, the article turns to address the role of opium and temporality in the interanimations of race and disability in two sites of 19th-century British empire: Langdon Down's clinic for idiocy, and China's retort on opium to Queen Victoria. The article concludes with a provocation that suggests yet another crossing of borders, that between researcher and researched: 'intoxicated method' is a hypothetical mode of approach that refuses idealised research positions by 'critically disabling' the idealised cognitive and conceptual lens of analysis.